Tyama-teeyt yookapa : interviews from the Meeting Point Project - Couzens, Vicki Louise, 1960-; Eira, Christina; Stebbins, Tonya N.; Victorian Aboriginal Corporation for Languages (Melbourne, Victoria : Victorian Aboriginal Corporation for Languages, 2014)
A collection of stories, reflections and hopes about language revival in Australian Aboriginal communities extracted from a series of interviews carried out during 2009-2010 Annotation pending.
A collection of stories, reflections and hopes about language revival in Australian Aboriginal communities extracted from a series of interviews carried out during 2009-2010.
Foreword by Jeanie Bell -- Introduction and dedication -- Interviews: Aunty Phyllis Hewitt; Aunty Caroline Briggs; Bruce Pascoe; Daryn McKenny; David Tournier; Doris Paton; Geoff Anderson; Jeanie Bell; Jenni Beer; Kevin Lowe; Lee Healy Lynnette Solomon-Dent; Maxine Jarrett; Tom Kinchela; Uncle Albert Mullett; Uncle Ivan Couzens -- Research team contributions: Vicki Couzens; Christina Eira; Tonya Stebbins -- Appendix: Interview guidelines.
Keywords: Australian languages -- Study and teaching; Language revival -- Australia; Language - Maintenance; Education - Language - Indigenous languages; Kurnai / Gunai language group (S68) (Vic SJ55); Boonwurrung / Boonerwrung / Bunurong people (S35) (Vic SJ55-09); Wathawurrung / Wada wurrung / Wathaurong language (S29) (Vic SJ54-12); Awabakal language (S66) (NSW SI56-05); Wiradjuri language (D10) (NSW SI55-07); Daungwurrung / Taungurong language (S37) (Vic SJ55-02); Gumbaynggir / Gumbainggirr language (E7) (NSW SH56-11); Language maintenance; Australian